Energy content of sublittoral biologically-relevant resources in the East Antarctic seas - Giginyak, Yu.G.; Lukashanets, Dz.A.; Borodin, O.I.; Miamin, V.E.; Baichorov, V.M. (Український антарктичний журнал, 2019)
Objective.To determine the energy value of several groups of the East Antarctic sea biota and identify potential calorific differences in the context of both taxa and ecological groups. Methodology. Sampling was carried out by traditional methods (benthic traps, diving gathering), and remote sampling was also applied (using remote-controlled underwater vehicles). The energy value of organisms is determined using wet burning methods.